War Criminals and Other "Ordinary Men": A Case Report†. (2nd March 2016) - Hough, George; Twemlow, Stuart W.
ABSTRACT: The authors provide a psychological portrait of Milan Lukić, a convicted war criminal, whose case was convened at the International Criminal Tribunal for the Former Yugoslavia at The Hague. Such in‐depth case studies are rare in the study of war criminals and unique to the study of war criminals associated with the Bosnian conflict. The authors relied upon extensive psychological interviews and psychological testing conducted over a series of days with Lukić and a review of extensive background records to create this psychological portrait. The evaluation data indicate that Lukić was found to be essentially "normal" psychologically, consistent with prior studies of war criminals who were also found to be psychologically normal and legally sane. Our findings contribute to the refutation of the so‐called Nazi personality hypothesis that emerged after World War II. There was no evidence from Lukic's developmental history that would be predictive of his war crimes behavior before the outbreak of the Bosnian conflict. The authors hypothesize that Lukic's war crimes behavior was, in part, a by‐product of the breakdown of the social and moral order that occurred in Bosnia. His ruthless and sadistic behaviors that were manifest after he entered the war suggest an emergent atypical pattern of psychopathic behaviors which manifested under conditions of extreme social and moral duress and which were also reinforced by blind obedience to authority. The authors advocate that future studies of war criminals include an examination of personality as embedded within a particularized social and historical context. Copyright © 2016 John Wiley & Sons, Ltd.